MANFAAT SUSU KEDELAI SEBAGAI TERAPI PENURUN KADAR GLUKOSA DARAH PADA KLIEN DIABETES MELLITUS (Study eksperimental di poli penyakit dalam RSUD Pare Kabupaten Kediri Tahun 2010) - Cahyono, Aris Dwi (Jurnal AKP, 2011)
Diabetes mellitus is a heterogeneous group of disorders characterized by an increase in the blood or hyperglycemia gluikosa (Brunner and Suddarth, 2002). Diabetes mellitus can affect other diseases such as coronary heart disease, stroke, gangrene / foot injuries, kidney failure, blindness, a sense of numbness, tingling and erectile dysfunction. The purpose of this study is to determine the effect of soy milk as a blood glucose-lowering therapy in clients with diabetes mellitus. The purpose of this study was to determine whether there is influence of soy milk to the reduction of blood glucose levels in diabetes mellitus clients.Design used in this research is experimental quasy two groups, namely the treatment and control groups, with pre and post treatment approaches. Population is all clients with diabetes mellitus who meet the criteria for inclusion and exclusion. Samples are some clients with diabetes mellitus who were 24 0rang, which is divided into 12 people 12 people were treated and controlled. Data analysis was done by comparing the level of blood glucose levels before and after treatment, analyzed by inferential were processed with SPSS software 14 to determine the average and standard deviation. The results show that the treatment group of some 12 people there is a decrease of blood glucose levels of 307.58 mg / dl to 247.42 mg / dl mmHg in other words the blood glucose levels decreased by 19.5%.From the description above we can conclude that there is a decrease in blood glucose levels in the group given soy milk therapy for five days in a row, means that soy milk can lower blood glucose levels in diabetes mellitus clients.